Imperatives of economic nature that have a negative impact on the legal provision of national security - Harasymiv, Taras; Chornopyska, Viktoriia; Zhukovska, Valentyna; Bek, Uliana; Voityk, Oleksandra (Edelweiss Applied Science and Technology, 2024)
The study represents the effort of applying neo-realism paradigm to the analysis of economic security factor in the system of national security and its legislative framing in various countries in regional view. Along with overall trends in global landscape of economic security, the cases of Pakistan, UK, USA, Australia, and China are considered. The article can serve as a methodological basis for subsequent scientific research in this area.